Phase evolution of strong-field ionization - Lynda Hutcheson; Maximilian Hartmann; Gergana D. Borisova; Paul Birk; Shuyuan Hu; Christian Ott; Thomas Pfeifer; Hugo W. van der Hart; Andrew C. Brown (Physical Review Research, 2025)
We investigate the time-dependent evolution of the dipole phase shift induced by strong-field ionization (SFI) using attosecond transient absorption spectroscopy (ATAS) for time delays where the pump-probe pulses overlap. We study measured and calculated time-dependent attosecond transient absorption spectra of the ionic 4d→5p in xenon, and present the time-dependent line shape parameters in the complex plane. We attribute the complex dynamics to the contribution of three distinct processes: accumulation of ionization, transient population, and retrapping of excited states arising from polarization of the ground state.